2020
DOI: 10.32607/actanaturae.10947
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the mRNA expression levels of calpains 1/2 and proteins involved in cytoskeleton remodeling

Abstract: Remodeling of the cytoskeleton underlies various cellular processes, including those associated with metastasis. The role of the proteases and proteins involved in cytoskeletal reorganization is being actively studied. However, there are no published data on the relationship between the mRNA expression levels of calpains 1/2 (CAPN 1/2) and the proteins associated with cytoskeleton remodeling. Therefore, the purpose of our study was to establish the relationship between the mRNA expression levels of CAPN 1/2 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…CAPN2 encodes calpain-2 catalytic subunit, which is a calcium-regulated non-lysosomal thiol-protease. It catalyzes limited proteolysis of substrates involved in cytoskeletal remodeling and signal transduction [ 40 ]. STMN1 encodes Stathmin, which is involved in the regulation of the microtubule filament system by destabilizing microtubules.…”
Section: Discussionmentioning
confidence: 99%
“…CAPN2 encodes calpain-2 catalytic subunit, which is a calcium-regulated non-lysosomal thiol-protease. It catalyzes limited proteolysis of substrates involved in cytoskeletal remodeling and signal transduction [ 40 ]. STMN1 encodes Stathmin, which is involved in the regulation of the microtubule filament system by destabilizing microtubules.…”
Section: Discussionmentioning
confidence: 99%
“…Switching between EMT and MAT can be quite fast and depends on the properties of the microenvironment. The participation of proteins of the Rho family GTPases is common to all migration routes [6,7,8,9]. The model of the mouse glioblastoma cell line showed that the induced expression of Rnd3 (Rho family-GTPases) inhibited the activity of Snail1, which blocked the migration of tumor cells [10].…”
Section: Introductionmentioning
confidence: 99%
“…CAPN1 belongs to the calpains family, and along with other members, is responsible for limited proteolysis of a variety of target substrates (39). Under physiological conditions, calpains are involved in numerous processes such as cytoskeleton remodeling, signal transduction pathway regulation, platelet activation, cell differentiation, and cell apoptosis (39)(40)(41). CAPN1 overactivation results in unregulated proteolysis and aberrant activation of signaling cascades, leading to cellular damage and ultimately cell death (42).…”
Section: Discussionmentioning
confidence: 99%